Advances in parasitology Volume eighty, [The epidemiology of plasmodium vivax : history, hiatus and hubris. Part A] - Hay, S. I. (Simon I.); Price, Ric.; Baird, J. Kevin (Kidlington, Oxford : Elsevier, 2012)
First published in 1963, Advances in Parasitology contains comprehensive and up-to-date reviews in all areas of interest in contemporary parasitology. Advances in Parasitology includes medical studies on parasites of major influence, such as Plasmodium falciparum and trypanosomes. The series also contains reviews of more traditional areas, such as zoology, taxonomy, and life history, which shape current thinking and applications. Eclectic volumes are supplemented by thematic volumes on various topics, including control of human parasitic diseases and global mapping of infectious diseases. The 2010 impact factor is1.683. * Informs and updates on all the latest developments in the field * Contributions from leading authorities and industry experts.
2. ESTABLISHED ANTI-TRANSMISSION MEASURES?3. DRUGS FOR CONTROL OF RELAPSING MALARIA;?4. DIFFICULTY GOING FROM LOW TO NO MALARIA TRANSMISSION;?5. SURVEILLANCE AS KEY INTERVENTION FOR MALARIA ELIMINATION;?6. PROBLEMS OF MALARIA REINTRODUCTION INTO ELIMINATED AREAS;?7. PROSPECTS FOR IMPROVED DRUGS FOR CONTROL/ELIMINATION;?8. PROSPECTS FOR IMPROVED ANTI-TRANSMISSION MEASURES;?9. CONCLUSIONS; ACKNOWLEDGEMENTS; REFERENCES; INDEX.
Includes bibliographical references and index.
Elsevier
Keywords: Parasitology; Medical parasitology; SCIENCE -- Life Sciences -- Zoology -- General; Parasitology; Electronic books